The valuation of the cultural heritage in the historical center of Zacatecas, Mexico - Raygoza Castro, Mariana Rubí (2020)
The aim of this article is to analyze the commercialization process, that is, the enhancement of the cultural heritage located in the Historic Center of Zacatecas (CHZ), since its appointment as a World Heritage Site in 1993 by UNESCO. By acquiring this category, exploitation dynamics have been developed in favor of some individuals and interest groups, thereby generating the dispossession of public spaces, the elitization of cultural consumption in the inhabitants, real estate speculation, and the revenue reallocation in the use of the land. As a result, a transformation process is observed for the tourist service for the benefit of an elite in power and not of the inhabitants themselves. This is evidenced by the analysis of statistical data, maps and bibliographic references.